Vaccine efficacy of COVID-19 in Bangladesh: Does vaccination prevent the pandemic? - Khan, Nuzhat Nuari; Begum, Shahin Ara; Afeef, Raheedun; Kamrujjaman, Md (GANIT: Journal of Bangladesh Mathematical Society, 2023)
We adopted a commonly used epidemiologic model known as Susceptible-Infectious-Recovered (SIR) by adding a compartment vaccination to locate the COVID-19 hotspot in Bangladesh. Using data from the Directorate General of Health Services (DGHS), we utilized the Susceptible-Vaccinated-Infectious-Recovered (SVIR) model to assess vaccine efficacy. Vaccination against COVID-19 has begun in industrialized nations and will be completed by early December 2020. Before 2023, mass vaccination for impoverished or low-income nations would be extremely difficult. Bangladesh, a lower-middle-income country, started a statewide COVID- 19 immunization effort in early February 2021. This study aimed to recognize the effectiveness of vaccination on the infected population in Bangladesh. Additionally, the study aimed to create public awareness of the importance of vaccination during a pandemic. GANIT J. Bangladesh Math. Soc. 43.1 (2023) 045- 062